DETERMINATION OF UJRAH ON WAREHOUSE COLLATERAL ACCORDING TO THE IJĀRAH 'ALĀ AL-MANĀFI' CONTRACT - Yashila Rahima; Yuhasnibar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article discusses the topic of determining ujrah on the storage of collateral for bags and warehouses at PT Pegadaian Syariah Banda Aceh according to the ijārah 'alā al-manāfi' contract. This article is conducted to know and analyse the value and legal status of determining ujrah related to collateral storage seen from the ijārah 'alā al-manāfi' contract. The approach used is a conceptual approach, type of empirical legal research, while the data is obtained from interviews and documentation studies. The data findings were analysed qualitatively with a prescriptive nature. The results showed that the determination of ujrah on the storage of collateral for bags or warehouses at PT Pegadaian Syariah Banda Aceh is in accordance with the ijārah 'alā al-manāfi' contract in Islamic fiqh and in the DSN-MUI Fatwa. The determination of ujrah is based on the estimated value of the collateral, not judged by the type of collateral, and not determined by the amount of the loan.